Grain boundary segregation-induced strengthening-weakening transition and its ideal maximum strength in nanopolycrystalline FeNiCrCoCu high-entropy alloys. (15th January 2023) - He, Tengwu; Qi, Yuming; Ji, Yanzhou; Feng, Miaolin
Highlights: Cu grain boundary segregation in nc-/nt-HEA stabilizes the microstructure. High Cu concentration at GBs induces strengthening-weakening transition. Detwinning processes significantly suppressed by segregation effect in nt-HEA. A theoretical model to assess critical GB segregation amounts was developed. Abstract: The combined Monte Carlo and Molecular Dynamics simulations were employed to explore the influence of elemental segregation at grain boundaries (GBs) on the mechanical properties of FeNiCrCoCu high entropy alloys under uniaxial load. The chemical potential difference with respect to Ni atoms was first obtained, and used to reach the equilibrium elemental distributions in sample models with different Cu contents, grain sizes and twin thicknesses. By comparing the random and segregated configurations, the role of GB segregation was analyzed in detail. It is found that the GB segregation trend is Ni<Fe<Co<Cr<Cu. The Cu atoms have no preference to segregate at coherent twin boundaries, and their dominant segregation at GBs prevents the detwinning that usually occurs in softening stage, further increasing twin strength. The segregation with low concentration at GBs can improve the strength by suppressing dislocation emission from GBs and further enhance the GB-mediated plastic deformation; while excessive segregation at GBs results in harmful weakening effect with GB cracking. The transition from strengthening to weakening is closely related to the GB segregated Cu concentration. To estimate the critical segregation amount in case of maximum strength, a theoretical model was established, where three regions (strengthening, transition and weakening) are distinguished. It is revealed that the strengthening region occupies a small area, and the addition of Cu contents should be rigorously tailored. This work deepens the understanding of the strengthening mechanisms arising from GB segregation and provides insights into the design of ultrahigh-strength materials. Graphical abstract: Equilibrium configurations of nc/nt (FeNiCrCo)1- x Cu x ( x = 4 at. %) high-entropy alloys for (a) random distributions for all alloy elements, (b) Cu segregation at GBs, (c) element random distributions and (d) Cu segregation with nt structures. Atoms colored in green, red, and white corresponds to face-centered cubic (FCC), hexagonal close-packed (HCP), and other crystal arrangements. Cu atoms are highlighted in dark blue. Image, graphical abstract